Sumberdaya Kuda Laut Hippocampus spp di Perairan Pulau Bintan Teluk Lampung dan Pulau Tanakeke - Masayu Rahmia Anwar Putri; Astri Suryandari; Joni Haryadi (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Seahorse Resources (Hippocampus spp.) in the Waters of Bintan Island, Lampung Bay and Tanakeke Island.Information on seahorse resources is very limited, from 35 species of marine species listed on the IUCN redlist, 20 species are listed as "data deficient" which illustrates the lack of information related to sea horses, even for highly exploited species. This research was conducted to inventory sea horse resources (Hippocampus spp.), covering spesies information, size, sex ratio and density of seahorses from three potential locations, they are Bintan Island, Lampung and Tanakeke Island Waters. Field observation for seahorse resources was conducted at Bintan Island (Riau Islands Province) in March 2016, Lampung Bay (Lampung Province) in May 2016 and Tanakeke Islands (Takalar Regency, South Sulawesi) in June 2016 by purposive sampling method, interview with fisherman and collector and also literature study. A total of 5 seahorse species were found in three research locations, 4 species found in Bintan waters (H. comes, H. spinossisimus, H. hystrix and H. kuda), 2 species found in Lampung Bay (H. comes and H. kuda) and only 1 species found in Tanakeke (H.barbouri). Most of seahorse found during the study were categorized as sexually mature, dominated with seahorse 11-12 cm in size. The different types and densities of seahorses in the three study sites are supported by differences in habitat where seahorses are occupied. The density of seahorses tended to be low due to over-exploitation, environmental change and habitat damage. Management measures based on biological aspects and ecological conditions of each region need to be carried out for sustainable seahorse fisheries.